Identifikasi Potensi Sumberdaya Pesisir Dan Laut Pulau Sabu Untuk Pemberdayaan Masyarakat Pesisir Di Kabupaten Sabu Raijua - Endeyani V. Muhamad (Politeknik Pertanian Negeri Kupang, 2012)
Potency Identificaton of Marine and Coastal Recources in Sabu Island for Community Empowerment in Sabu Raijua District. Research on coastal and marine resource potential for empowerment Sabu Island coastal communities in the District of Sabu Raijua was implemented in 2009 aimed at identifying: 1) the nature conditions; b) infrastructure and accessibility; c) the profile of coastal communities and the use of marine and coastal resource. The method used in this study was a survey of potential natural resources as well as human resources and literature review for the two conditions. The results showed that: 1) The condition of coastal and marine resources on the island of Sabu which could potentially be developed to empower the coastal communities were fish and non fish, but it was seaweed that developed well and has been cultivated in commercial scale. Technology of aquaculture and marine capture that were applied by the community was very simple with minimal output per capita. 3) Availability of main and supporting infrastructure including public transportation by land, sea and air were limited, streets hardeningÂ need to be expanded, at the same time, range and duration of illumination by electricity power need to be expandedÂ for 24 hours a day. 4). The strength of cultural values system in society with a lifestyle of giving resulted on the high social costs. Recommedation developed based on the conclusion were: 1). Priority development of the potential of coastal and marine resources were directed at non commodity fish and the seaweed due to the population of coastal areas on the Sabu Island independently has developed business with commercial value which was impacted on per capita on society. On the other side, coastal resources had the potency in the increasing of business scale. 2). The development ofresidential total area and transportation infrastructure that support economic growth therefore can suppress the high social costs.Key words:Â Resources of Coastal and Marine, Community, Empowerment